Effects of pantogam active on behavior and neuroreceptor spectrum in mouse model of attention deficit disorder - N. A. Sukhorukova; E. V. Vasileva; E. A. Kondrakhin; R. M. Salimov; G. I. Kovalev (LLC "Publisher OKI", 2022)
Effect of Pantogam active subchronic administration (200 mg/kg/day, i.p.) on the behavior of outbred CD-1 mice in the experimental model of attention deficit disorder was studied in the "closed enriched cross maze" test. Pantogam active corrected the initial attention deficit of ED-low rodents subpopulation without changing other parameters of their behavior. Analysis of the results of radioligand binding revealed statistically significant differences in the distribution of D2 and GABAB-receptors in the brain structures of outbred CD-1 mice subpopulations. In the prefrontal cortex (PFC) of ED-low control group with reduced attention level, compared with ED-high control, density of D2 receptors was higher by 18 %, while density of GABAB receptors was lower by 35 %. Administration of pantogam active resulted in decreasing of D2 receptors density by 23 % and increasing of this indicator by 42 % for GABAB- receptors in the PFC of ED-low animals, respectively. Thus, this studied drug has potential efficacy in treating attention deficit in experimental animals, normalizes behavior and possible molecular markers of this pathology.